DERIVATIONAL SUFFIXES NOUN DERIVED FROM VERB FOUND IN CNN NEWS POLITIC - Setya Darma, I Ketut Egik (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This research titled "Derivational Suffixes Noun Derived from Verb Found in CNN News Politic”. The method used in this research is descriptive quantitative method to identify the type and development of suffix derived nouns found in the data source. This research found a total of 29 data from 7 political news in 2023 sourced from CNN News. The author uses the theory from Plag (2002) as a reference in conducting the analysis. This theory claims that there are twenty-two types of derivation noun suffixes -ness, -age, -al, -ship, -an, -ance, -ing, -ion, - ant, -ism, -ist, -cy/-ce, -ity, -ment, -dom, -ee, -eer, -(e)ry, -ess, -ful, -hood, -er. However, in this study only found four types of suffixes out of twenty-two, including: suffix -ment (31.1%), suffix -er (10.3%), suffix -ing (48.3%), and suffix -ion (10,3%).